Significant Capacitance Performance of Vertically Aligned Single-Walled Carbon Nanotube Supercapacitor by Varying Potassium Hydroxide Concentration - Mohd Abid, Mohd Asyadi Azam (ESG, 2013)
In this manuscript, the effect of potassium hydroxide (KOH) electrolyte concentrations (0.1 M, 1.0 M, and 6.0 M) to the specific gravimetric capacitance of vertically aligned single-walled carbon nanotube (VA-SWCNT) based supercapacitor will be reported. VA-SWCNT electrode was prepared using direct growth technique of alcohol catalytic chemical vapor deposition. It was found that specific gravimetric capacitance of the VA-SWCNT supercapacitors increased with increasing KOH electrolyte concentration. Besides, lower concentration (or viscosity) of the KOH electrolyte may give better stability in charge storage performance; suggesting difference of ion movement inside the VA-SWCNT double-layer system. The capacitance slope (as a function of cyclic voltammetry scan rate) can be improved by lower concentration of the electrolyte.